Removal of Ammonia and Colour from Landfill Leachate using Integrated Electrocoagulation-Zeolite Adsorption Processes - Akbar, Nor Azliza; Ismail, Badrul Nizam; Mohd Zin, Nur Shaylinda; Said, Mohamad Sazali (International Journal of Integrated Engineering, 2024)
The amount of waste generated in Malaysia had increased annually due to both economic and population accelerations. This resulted in an increase in leachate production that contains a high amount of ammonia nitrogen (NH3-N) and colour, which is a severe problem for both environments as well as for human health. Therefore, this study aimed to determine the potential of Electrocoagulation (EC) – zeolite adsorption for removing NH3-N and colour from landfill leachate. In the experimental works, two batch studies consist of batch EC using aluminium (Al) cylindrical electrode and batch adsorption study using clinoptilolite zeolites adsorbent were conducted using leachate sample collected from Pulau Burung Sanitary Landfill (PBSL). The batch EC experiment was carried out to determine the optimum removal of NH3-N and colour by the effect of current density (7 - 35 mA/mm2), initial pH (5 - 9), electrolysis time (0 - 90 minutes) and inter-electrode distance (5 - 25 mm). An integrated EC - zeolite adsorption was carried out under the optimum condition of 2.0 g/150 mL adsorbent dosage, contact time of 100 minutes and an initial pH value of 8. Based on the experiment, almost 50% of NH3-N and 95% of colour were removed using a single EC under the optimum current density of 14.0 mA/mm2, pH 5, electrolysis time of 75 minutes and 15 mm of inter-electrode distance. A comparison of colour removal between single EC and EC-Zeolite showed the same degradation performance. The interaction of hydrogen ion (H+) with aluminium hydroxide ion (Al (OH)3) produces during EC stabilises small particles forming larger sludge that reduces colour concentration. The removal of NH3-N increased from 50.0% to 93% when EC was integrated with clinoptilolite zeolite adsorption. In conclusion, the results show that both processes can potentially remove colour while the integrated process effectively removes NH3-N from landfill leachate. The proposed treatment helps optimise process performance while minimising the operational cost of the treatment. Thus, the proposed integrated EC – zeolite adsorption processes can be an alternative to landfill leachate treatment which aligns with the 12th Malaysia Plan to reduce pollution and carbon emissions to become a carbon neutral nation as early as 2050.